Land Access, Tenure and Investment in Post-War Northern Mozambique - Tilman Brück (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
The relationship between land investment and tenure security is usually tested in land scarce but peaceful areas. This article examines instead the effects of land abundance and war for investment and tenure security. The paper demonstrates that war enhances land abundance. This implies that farm size for the analysis of land investment and tenure security. The paper formally tests for land abundance and estimates a system of equations using farm survey data from post-war Mozambique. Farm size is found to be a key determinant of both investment and tenure security. This raises important policy issues for post-war reconstruction.
Keywords: O13; Q12; Q15; O12; 330; land; property rights; tenure security; investment; war; conflict; reconstruction; policy; Mozambique; Africa; Agrarboden; Landwirtschaftliches Betriebssystem; Betriebsgrösse; Investition; Kriegsfolgen; Kriegsschaden; Theorie; Mocambique; tenure security